Teknik Restrukturisasi Kognitif untuk Menurunkan Mogok Sekolah pada Siswa SMP - Probowati, Devy; Triyono, Triyono; Radjah, Carolina Ligya (Konseling Edukasi : Journal of Guidance and Counseling, 2020)
Cognitive Restructuring Techniques to Reduce School Strikes in Middle School Students. This study aims to observe cognitive restructuring techniques in reducing junior high school strike students. This study uses an experimental method through six stages using a single subject design with A-B-A design. The baseline phase (A) was carried out for three sessions, the intervention phase (B) was carried out for six sessions, and the baseline phase (A ') was carried out for three sessions. The results showed that in the baseline phase (A) each subject was still in the same condition, the intervention phase (B) of each subject was in a stable condition, and the baseline phase (A ') of each subject had shown difference. Therefore, it can be concluded that there is a difference from before being given an intervention to after being given an intervention using cognitive restructuring techniques to reduce school strikes of junior high school students with the category of reducing the level of school strike each subject is different.Keywords: Cognitive Restructuring Techniques, Strike, School